Molecular Basis of Cardiac and Vascular Injuries Associated With COVID-19 - Hachim, Mahmood Yaseen; Al Heialy, Saba; Senok, Abiola; Hamid, Qutayba; Alsheikh-Ali, Alawi (Frontiers in Cardiovascular Medicine, 2020)
Background: Coronavirus disease 2019 (COVID-19) is a viral respiratory illness caused by the novel coronavirus SARS-CoV-2. The presence of the pre-existing cardiac disease is associated with an increased likelihood of severe clinical course and mortality in patients with COVID-19. Besides, current evidence indicates that a significant number of patients with COVID-19 also exhibit cardiovascular involvement even in the absence of known cardiac risk factors. Therefore, there is a need to understand the underlying mechanisms and genetic predispositions that explain cardiovascular involvement in COVID-19. Objectives:In silico analysis of publicly available datasets to decipher the molecular basis, potential pathways, and the role of the endothelium in the pathogenesis of cardiac and vascular injuries in COVID-19. Materials and Methods: Consistent significant differentially expressed genes (DEGs) shared by endothelium and peripheral immune cells were identified in five microarray transcriptomic profiling datasets in patients with venous thromboembolism “VTE,” acute coronary syndrome, heart failure and/or cardiogenic shock (main cardiovascular injuries related to COVID-19) compared to healthy controls. The identified genes were further examined in the publicly available transcriptomic dataset for cell/tissue specificity in lung tissue, in different ethnicities and in SARS-CoV-2 infected vs. mock-infected lung tissues and cardiomyocytes. Results: We identified 36 DEGs in blood and endothelium known to play key roles in endothelium and vascular biology, regulation of cellular response to stress as well as endothelial cell migration. Some of these genes were upregulated significantly in SARS-CoV-2 infected lung tissues. On the other hand, some genes with cardioprotective functions were downregulated in SARS-CoV-2 infected cardiomyocytes. Conclusion: In conclusion, our findings from the analysis of publicly available transcriptomic datasets identified shared core genes pertinent to cardiac and vascular-related injuries and their probable role in genetic susceptibility to cardiovascular injury in patients with COVID-19.